Penerapan Sistem Informasi Website Desa Dolopo Dalam Pelayanan Publik Di Desa Dolopo Kecamatan Dolopo Kabupaten Madiun - Purwandari, Nur Alifia; Prasetyawan, Agus (Jurnal Inovasi Administrasi Negara Terapan, 2024)
The implementation of Dolopo Village's website information system is still fairly ineffective. To increase the value of information systems in public services, Dolopo Village decided to create a website called "website desadolopo.com" so that all information systems and services can be reached by the wider community. In PERBUP Madiun Regency No. 2 of 2020 concerning Network Management of Legal Documents and Information within the Government of Madiun Regency in Article 13 concerning Structuring Legal Information Systems Number 3 that the utilization of information and communication technology is carried out through an internet/website system. This research method is descriptive qualitative with data collection by observation, interview and documentation. The conclusion of this research is that the application of the Dolopo Village website information system has not been running effectively due to the obstacle of the lack of technological knowledge of the Dolopo Village operator. The suggestion that can be given is the holding of training/socialization for handling technology development for the Dolopo Village government, so that they no longer use third party services if there are obstacles or problems that occur in the application of the Dolopo Village website information system. Based on the observation, there are several obstacles and barriers in the implementation of the Dolopo Village website information system, causing a lack of information dissemination related to Dolopo Village and constraints due to the lack of technological knowledge of operators in the implementation of the Dolopo Village website information system. Keywords: Implementation, Egovernment, Service.